Novel pilot protection based on time‐domain for transmission line with doubly fed induction generator. (22nd July 2020) - Yang, Qifan; Ma, Hongzhong; Liu, Yiqing; Duan, Dawei
Summary: Large‐scale doubly fed induction generator (DFIG) wind farms are integrated into power grid through transmission line. Traditional pilot protection as the main protection is widely used in transmission line. However, when traditional pilot protection is applied to transmission line with DFIG, it may appear undesired tripping. Therefore, this work presents a novel pilot protection based on time‐domain waveform identification for transmission line with DFIG. The waveform features of the fault currents provided by DFIG and synchronous generator are analyzed. According to the waveform similarity between prefault and postfault currents, calculated separately at DFIG wind farm side and power grid side, the protection principle is established: when internal faults occur, the waveform similarity calculated at DFIG wind farm side is much lower than that calculated at power grid side; when external faults occur, the waveform similarity calculated at both sides are almost the same. A complete protection flow based on proposed principle is designed. Furthermore, a false data detection method is raised for resisting the influence of noise on the performance of proposed protection. Extensive digital simulations are conducted to verify the principle. The test results indicate that the proposed protection can reliably identify the internal faults and external faults, and also has strong ability to withstand the effects of fault resistance, noise, and communication delay.